Challenging power and unearned privilege in physiotherapy: lessons from Africa - Lurch, Stephanie; Cobbing, Saul; Chetty, Verusia; Maddocks, Stacy (Frontiers in Rehabilitation Sciences, 2023)
Power and privilege in the profession of Physiotherapy resides in the Western English-speaking world. Rehabilitation curricula and practices in the rest of the world are derived primarily from European epistemologies. The work of African thinkers and writers and African philosophies related to healthcare are not well known across the globe. In this paper, we will introduce readers to African philosophies such as Ubuntu and Seriti and describe how these ways of thinking challenge Western biomedical approaches to health care. A better appreciation and understanding of the communities in which people live and the interconnectedness of their relationships, will assist patients in attaining the health outcomes that they seek. We further make a call for Western professionals and researchers to make space for their African counterparts and practice genuine, critical allyship that stands to benefit everyone. By utilizing this knowledge to challenge practices and systems that oppress equity-denied populations, we believe that we can move towards a diversity of practitioners and practices that help to ensure better outcomes for all.